The effect of Gunn's intramuscular stimulation for postherpetic neuralgia -A report of 4 cases - Jung, Wook; Lee, Byung-Jun; Kim, Sin Sung; Lee, Young Jin (Korean journal of anesthesiology, 2010)
Herpes zoster is the consequence of reactivation of latent varicella zoster virus from dorsal root ganglia. Postherpetic neuralgia (PHN) may be diagnosed when pain persists in a dermatomal pattern long after the vesicular erruption has healed. PHN is a kind of neuropathic pain. The pathophysiology of PHN is uncertain, but neuropathic pain due to denervation supersensitivity may be important to understand the pathophysiology of PHN. Numerous treatment have been introduced for the management of PHN, but no methods that results in complete remission. Gunn's intramuscular stimulation (IMS) is one of the best treatment of chronic pain, especially neuropathic pain. We tried Gunn's IMS for treatment of PHN patients affecting thoracic dermatomes. As a result, the visual analogue scale (VAS) was decreased from 7-8 to 2-3 and the result were satisfactory. The purpose of this case report is to introduce the Gunn's IMS and review our experience for the treatment of PHN.